2021
DOI: 10.3389/fcvm.2021.736163
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive vs. Liberal Red Blood Cell Transfusion Strategy in Patients With Acute Myocardial Infarction and Anemia: A Systematic Review and Meta-Analysis

Abstract: Objective: Anemia is frequent in patients with acute myocardial infarction (AMI), and the optimal red blood cell transfusion strategy for AMI patients with anemia is still controversial. We aimed to compare the efficacy of restrictive and liberal red cell transfusion strategies in AMI patients with anemia.Methods: We systematically searched PubMed, EMBASE, Web of Science, Cochrane Library, and Clinicaltrials.gov, from their inception until March 2021. Studies designed to compare the efficacy between restrictiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Previous literature has investigated the impact of transfusion thresholds on mortality in the general ICU population. However, the effects of a restrictive transfusion protocol for ECMO patients are underreported in the literature (3, 4, 8, 12). The most important finding of this study was that a restrictive transfusion threshold was not associated with decreased rates of survival for patients on venoarterial ECMO, venovenous ECMO, or ECPR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature has investigated the impact of transfusion thresholds on mortality in the general ICU population. However, the effects of a restrictive transfusion protocol for ECMO patients are underreported in the literature (3, 4, 8, 12). The most important finding of this study was that a restrictive transfusion threshold was not associated with decreased rates of survival for patients on venoarterial ECMO, venovenous ECMO, or ECPR.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled clinical trial of non-ECMO critical care patients by the Canadian Critical Care Trials Group first reported that a RBC restrictive transfusion strategy of 7 g/dL was not associated with significantly increased patient mortality compared with a liberal transfusion strategy of 10 g/dL (8). Since this landmark study, multiple studies in the critical care patient population have also reported noninferior patient outcomes with a restrictive transfusion strategy (3,(12)(13)(14)(15)(16). Due to the limited clinical evidence of transfusion protocols in the ECMO population, many established transfusion protocols are currently based on extrapolated knowledge from research in critically ill patients (3).…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47][48][49] Combined with evidence suggesting RBC transfusion may not eliminate the risk of organ dysfunction and is associated with impaired outcomes, transfusion best practices remain elusive. 2,43,50,51 Contributing to uncertainty, 2 large randomized controlled trials in cardiac surgery did not show an impaired outcome with a more liberal transfusion strategy compared to a restrictive regimen. 47,48 Adding even more confounders, a recent large retrospective analysis in healthcare data from >700,000 patients showed that non-White ethnicity was associated with increased rates of blood transfusion.…”
Section: Updates On Transfusion Studies In Cardiac Surgerymentioning
confidence: 99%